Combination Therapy With Neuraminidase and Polymerase Inhibitors in Nude Mice Infected With Influenza Virus. (25th November 2017) - Kiso, Maki; Lopes, Tiago J S; Yamayoshi, Seiya; Ito, Mutsumi; Yamashita, Makoto; Nakajima, Noriko; Hasegawa, Hideki; Neumann, Gabriele; Kawaoka, Yoshihiro
Abstract : Immunocompromised mice were infected with an influenza virus and treated with viral neuraminidase or polymerase inhibitors, or combinations thereof. Combination therapy increased survival times but did not prevent the emergence of variants resistant to neuraminidase inhibitors. Abstract: Background: Treatment of immunocompromised, influenza virus–infected patients with the viral neuraminidase inhibitor oseltamivir often leads to the emergence of drug-resistant variants. Combination therapy with compounds that target different steps in the viral life cycle may improve treatment outcomes and reduce the emergence of drug-resistant variants. Methods: Here, we infected immunocompromised nude mice with an influenza A virus and treated them with neuraminidase (oseltamivir, laninamivir) or viral polymerase (favipiravir) inhibitors, or combinations thereof. Results: Combination therapy for 28 days increased survival times compared with monotherapy, but the animals died after treatment was terminated. Mono- and combination therapies did not consistently reduce lung virus titers. Prolonged viral replication led to the emergence of neuraminidase inhibitor–resistant variants, although viruses remained sensitive to favipiravir. Overall, favipiravir provided greater benefit than neuraminidase inhibitors. Conclusions: Collectively, our data demonstrate that combination therapy in immunocompromised hosts increases survival times, but does not suppress the emergence of neuraminidase inhibitor–resistant variants.